Biological characteristics of SARS-CoV-2 resistant populations by integrated gut microbiota sequencing, metabolomics, and proteomics: a cohort comparison study - Huachong Xu; Haoxuan Li; Junhao Xu; Yaoxin Chen; Li Deng; Xiaoyin Chen; Yinji Xu; Yinji Xu (Frontiers in Medicine, 2025)
ObjectiveMost research reports on COVID-19 infections have focused on the correlation between the severity of the disease symptoms and immune deficits, while the mechanisms affecting the susceptibility to SARS-CoV-2 remain largely unknown. The study aimed to comprehensively analyze the differences in immunity, gut microbiota, metabolism, and proteomics between the SARS-CoV-2 resistant population and the susceptible population.Methods and resultsIn this cohort comparison study, participants were rigorously selected based on inclusion and exclusion criteria in a continuous enrollment manner using combined questionnaires and clinical data, ultimately including 25 SARS-CoV-2 resistant volunteers versus 16 SARS-CoV-2 infected patients. The clinical information of the participants was recorded in detail, and fecal and blood samples were collected in a standardized manner for subsequent multi-omics analysis, including gut microbiota sequencing, metabolomics, and proteomics. This study has preliminarily elucidated the characteristics of the gut microbiota, serum metabolites, and serum proteins in the SARS-CoV-2 resistant population. It exhibits a unique metabolic signature characterized by elevated levels of serum phosphatidylinositol and the abundance of Prevotella, which may serve as a potential predictive biomarker for resistance to SARS-CoV-2.ConclusionGiven the crucial role of phosphatidylinositol in cell membrane architecture and viral infectivity, this study provides a promising entry point for further research into the pathogenesis and prevention strategies of COVID-19.